THE STUDENTS’ PERCEPTION OF EXTENSIVE READING IN ONLINE LEARNING AT FLSP CLASS - M Nabris Raunaq; Mutmainnah Mustofa; Elvin Nur Habibah (Journal of English for Academic and Specific Purposes (JEASP), 2021)
The purpose of this research aimed to know the students’ perception on their online Extensive reading learning. Survey design was used to conduct this study, and therefore, the questioner was constructed as the instruments of the study besides the researcher himself. The participants of this research were 44 students of first semester in the Accounting Department at FLSP class of University of Muhammadiyah Malang (Class A). The researcher adopted the questionnaire from a previous study conducted by Yogurtcu (2013), Tseng (2015), and Torres (2017), and the questionnaire showed the students’ perceptions of their online learning. The questionnaire consists of 20 statements and each statement has five alternative responses from 1 to 5: Strongly disagree, disagree, neutral, agree, and strongly agree. Google Form is the media to distribute the questionnaire due to the global pandemic of Covid 19. The results of the study indicate that students show positive response towards the use of Extensive reading in online learning. The students perceived that benefits of the activities had substantial effect on increasing their vocabularies, and students focused on educational evaluation they read during the semester. Based on the data, there are advantages, they are: we can complete to read the whole text, we can determine mind idea and supporting idea of the texts, The online reading activities helped me to get more interested in reading text, we can easily understand the text from online reading activities, and there is disadvantage, they are: distraction (Tools and Signal).